Do Sistema Personalizado de Ensino à educação online, aberta e massiva: uma análise historiográfica - Marinho, Vitor Duncan (2020)
From a historical-bibliographic analysis, this work identifies and analyzes contributions that Behavior Analysis has to offer to MOOCs (Massive Open Online Courses), through PSI (Personalized System of Instruction): (a) pedagogical advantages, adaptation facilities and possibilities to meet educational demands present in the Brazilian reality; and (b) pedagogical limitations, obstacles to adaptation and barriers imposed by current Brazilian legislation. MOOCs are distance courses, designed to serve an unrestricted number of participants, developed online and open to the public, which constitute an educational movement aimed at greater accessibility and inclusion in education through the internet. The PSI is a pedagogical method developed by Keller, Bori, Azzi and Sherman in the 1960s that has as its principles: (1) mastery requirement of the units; (2) specification of teaching objectives based on social demands; (3) individualized rhythm; (4) progressive units; (5) possibility of repetition of evaluations; (6) immediate feedback; (7) credit for success instead of penalty for errors; (8) lectures and demonstrations as a vehicle for motivation; (9) availability of study material with an emphasis on the written word; and (10) use of proctors. In addition to the history of PSI and MOOCs, this work uses in its analysis: experiences in MOOCs and PSI described in previous research; topics of current Brazilian legislation related to Distance Education (DE); and data related to Brazilian education. We conclude, for now, that although a MOOC based on PSI is possible, as there are no contradictions in relation to one another, there are obstacles in developing a “personalized” course for an unrestricted number of participants. On the other hand, some characteristics of the PSI are easily reached in MOOCs. Due to the current legislation, MOOCs are only applicable to Higher Education and free courses can become an important tool in a country with great inequality in access to education. While PSI can bring effective teaching to MOOCs, MOOCs can bring inclusion and accessibility to PSI, also providing a "showcase" through which its successes and mistakes can be better perceived by educators and the general public